Ships, Machinery and Mossback - Bowen, Harold Gardiner, 1883-1965 (Book collections on Project MUSE., 1954)
As Chief of the Bureau of Engineering, as Director of the Naval Research Laboratory, as industrial troubleshooter for Forrestal, Admiral Bowen frequently was forced to fight the "mossbacks" who stubbornly resisted new inventions and techniques. He was instrumental in the development of high-pressure high-temperature steam for ship turbines, diesel engines, radar, and other innovations which enabled our Navy to fight so successfully in World War II. Originally published in 1954. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905